Data processing and adjustment - Awange, Joseph (2018)
© Springer International Publishing AG 2018. In this chapter, the necessary data processing or post-processing following field measurements is presented. First, the general procedures undertaken to process baseline data are considered, followed by the adjustment of network observations.